2021
DOI: 10.1111/jocd.14398
|View full text |Cite
|
Sign up to set email alerts
|

An expert consensus report on the clinical use of the Vycross® hyaluronic acid VYC‐25 L filler

Abstract: Background:The portfolio of hyaluronic acid (HA) fillers and the techniques of administration have evolved in recent years. The latest innovation in the Vycross ® range was the introduction of VYC-25L (Juvéderm Volux ® ; Allergan plc), a first-in-class filler effective for chin and facial lower third remodeling. The aim here was to provide clinicians who are starting to use VYC-25L with key advice, and to standardize procedures so that optimal and predictable outcomes can be obtained. Methods: A multidisciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Volux ® uses Vycross™ technology and has the highest concentration of HA of the Juvéderm product line (25 mg/mL), with results lasting about 18 months. 34 A phase 3, multisite, randomized, no-treatment controlled study was completed in the United States in July 2021, with the goal of FDA approval in the United States in the near future. 35 Juvéderm Volite ® XC is also seeking FDA approval in the US for improvement of overall skin topography on the head and neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volux ® uses Vycross™ technology and has the highest concentration of HA of the Juvéderm product line (25 mg/mL), with results lasting about 18 months. 34 A phase 3, multisite, randomized, no-treatment controlled study was completed in the United States in July 2021, with the goal of FDA approval in the United States in the near future. 35 Juvéderm Volite ® XC is also seeking FDA approval in the US for improvement of overall skin topography on the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Juvéderm Volux®, which was recently approved in the EU for chin and facial lower third remodeling. Volux® uses Vycross™ technology and has the highest concentration of HA of the Juvéderm product line (25 mg/mL), with results lasting about 18 months 34 . A phase 3, multisite, randomized, no‐treatment controlled study was completed in the United States in July 2021, with the goal of FDA approval in the United States in the near future 35…”
Section: Discussionmentioning
confidence: 99%
“…In our practice, Volux is now becoming the product of choice for injecting the nose. It has the highest HA concentration within the Vycross range (25 mg/ml), and comparative preclinical analyses suggest that it also has the highest cohesivity and G′ 3,22,24 . In a recent Italian study, Volux was found to be safe and effective for treatment of the nose, 15 and ultrasound analysis has shown that it integrates completely into the tissue within 30 days of implantation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…To reduce product spreading, all procedures were performed using HA fillers with high G′ (and ideally also with high cohesivity). 22,23 In the nose, these specific rheological properties are more important than the particular product range used, and the "fivepoint liquid rhinoplasty" should be feasible using any appropriate HA filler with proven safety and efficacy. Nonetheless, 19 of the 20 patients in the present analysis received fillers from the Vycross range (Voluma or Volux).…”
Section: Ta B L E 1 Treatment Volumesmentioning
confidence: 99%
See 1 more Smart Citation